DSP implementation of surround speaker virtualizer for sound bar systems - N. Kaprocki; J. Kovačević; R. Pečkai Kovač; M. Malko (Telfor Journal, 2017)

(untitled)
This paper describes one solution for an implementation of the surround speaker virtualization module for a digital signal processor in a sound bar system. The main problem in this system, which consists of a decoder, a renderer and a post-processing module, is complex processing of sound in real-time. In order to achieve real-time execution of these operations and offer customers an affordable product, sound bar system is implemented on an embedded platform. A detailed overview of the system architecture and available resources is given, as the development of modules in an embedded system requires optimal resource usage. Furthermore, numerous challenges and constraints of real-time system programming are presented through the implementation of surround virtualization module, an integral part of the post-processing block. The merits of the proposed architecture are fortified with the measured usage of limited processor resources, and evaluation results confirm that real-time execution of the proposed solution is achieved.